From Energy Integration to Photon Counting: Redefining the Design and Performance of Clinical CT. - Carvalho, Henrique; Noël, Peter B.; Jha, Saurabh; Jamal, Faisal (Applied Radiology, 2026)
Computed Tomography (CT) has advanced continuously since the 1970s, evolving from static brain imaging to high-speed, high-resolution volumetric and spectral systems. This review outlines key milestones leading to photon-counting CT (PCCT) and how it addresses the fundamental limitations of energy-integrating detector (EID) technology. While innovations such as helical scanning, multidetector arrays, dual-source systems, and iterative reconstruction (IR) have improved image quality and reduced dose, EID-CT remains constrained by electronic noise, limited spatial resolution, and limited accessibility of spectral information. PCCT introduces direct-conversion detectors that count and classify individual x-ray photons by energy, delivering improved spatial and contrast resolution, intrinsic spectral data, and noise-efficient imaging. PCCT unites ultra-high-resolution, enhanced contrast-to-noise ratio, and multienergy capability in every scan. Early clinical results demonstrate substantial benefits in cardiovascular, pulmonary, musculoskeletal, and oncologic imaging. As PCCT enters routine practice, it marks a paradigm shift toward data-rich, spectrally resolved imaging with greater diagnostic precision and efficiency.